Mitochondrial DNA evolution in the obscura species subgroup of Drosophila. - Gonzalez, A.M.; Hernandez, M.; Volz, A.; Pestano, J.; Larruga, J.M.; Sperlich, D.; Cabrera, V.M. (Journal of Molecular Evolution, 1990)
Mitochondrial DNA (mtDNA) restriction site maps for nine species of the Drosophila obscura subgroup and for Drosophila melanogaster were established. Taking into account all restriction enzymes (12) and strains (45) analyzed, a total of 105 different sites were detected, which corresponds to a sample of 3.49% of the mtDNA genome. Based on nucleotide divergences, two phylogenetic trees were constructed assuming either constant or variable rates of evolution. Both methods led to the same relationships. Five differentiated clusters were found for the obscura subgroup species, one Nearctic, represented by Drosophila pseudoobscura, and four Palearctic, two grouping the related triads of species Drosophila subobscura, Drosophila madeirensis, Drosophila obscura, Drosophila subsilvestris, and two more represented by one species each, Drosophila bifasciata, and Drosophila tristis. The different Palearctic clusters are as distant between themselves as with the Nearctic one. For the related species D. subobscura, D. madeirensis, and D. guanche, the pair D. subobscura-D. madeirensis is the closest one. The relationships found by nucleotide divergence were confirmed by differences in mitochondrial genome size, with related species sharing similar genome lengths and differing from the distant ones. The total mtDNA size range for the obscura subgroup species was from 15.5 kb for D. pseudoobscura to 17.1 for D. tristis.